Hubble space telescope observations of accretion-induced star formation in the tadpole galaxy Kiso 5639 - Elmegreen, Debra Meloy; Elmegreen, Bruce G.; Almeida, Jorge Sánchez; Muñoz-Tuñón, Casiana; Mendez-Abreu, Jairo; Gallagher, John S.; Rafelski, Marc; Filho, Mercedes; Ceverino, Daniel (The astrophysical journal, 2016)
The tadpole galaxy Kiso 5639 has a slowly rotating disk with a drop in metallicity at its star-forming head, suggesting that star formation was triggered by the accretion of metal-poor gas. We present multi-wavelength Hubble Space Telescope Wide Field Camera 3 images of UV through I band plus Hα to search for peripheral emission and determine the properties of various regions. The head has a mass in young stars of and an ionization rate of s−1, equivalent to ∼2100 O9-type stars. There are four older star-forming regions in the tail, and an underlying disk with a photometric age of ∼1 Gyr. The mass distribution function of 61 star clusters is a power law with a slope of −1.73 ± 0.51. Fourteen young clusters in the head are more massive than , suggesting a clustering fraction of 30%-45%. Wispy filaments of Hα emission and young stars extend away from the galaxy. Shells and holes in the head H ii region could be from winds and supernovae. Gravity from the disk should limit the expansion of the H ii region, although hot gas might escape through the holes. The star formation surface density determined from Hα in the head is compared to that expected from likely pre-existing and accreted gas. Unless the surface density of the accreted gas is a factor of ∼3 or more larger than what was in the galaxy before, the star formation rate has to exceed the usual Kennicutt-Schmidt rate by a factor of .
Gesehen am 06.05.2020